IMPLEMENTASI PROGRAM LONG INTERDISCIPLINARY COMMUNITY CARE (PoLICe) DIMASA PANDEMIK COVID-19 DI KOTA YOGYAKARTA - Wantonoro Wantonoro; Suri Salmiyati; Nur Faidati (Jurnal Abdi Insani, 2023)
The Special Region of Yogyakarta has the highest proportion of elderly population in Indonesia, accompanied by a very high prevalence of various chronic diseases. COVID-19 positive patients who have comorbidities such as diabetes mellitus (DM) pneumonia, kidney failure and hypertension have a poor prognosis and a high mortality rate. Health service assistance is needed that is long-term care directly in the community to reach and maintain and improve conditions, prevent further severity and complications during the COVID-19 pandemic. The Long Interdisciplinary Community Care Program at 'Aisyiyah University Yogyakarta (PoLICE_Unisa) provides information on the need to improve long-term care services specifically based on the principles of patient centered care in the community. (1) forming and optimizing village health cadres that are integrated with the PoLICE_Unisa team, (2) screening educational needs in the community (3) comprehensive education about chronic disease management. The evaluation was carried out by evaluating the condition of the community individually, such as the absence of complications and the severity of the disease, both objectively and subjectively. after going through general health screening, in the end there were six patients/families who were identified as having chronic disease problems; stroke, diabetes mellitus and hypertension who are then willing to be directly involved in this activity. The involvement of all components, namely health cadres, families and patients as well as teams consisting of several professions, has provided integration and collaboration that can be continuously improved to improve the level of health for people in need. this activity provides things that are felt to be meaningful for the health status of families/patients directly, especially in the management of chronic diseases.